Nonlinear response of methane release to increased trophic state levels coupled with microbial processes in shallow lakes. (October 2020) - Zhou, Yiwen; Song, Kang; Han, Ruiming; Riya, Shohei; Xu, Xiaoguang; Yeerken, Senbati; Geng, Shixiong; Ma, You; Terada, Akihiko
Abstract: Shallow lakes are a crucial source of methane (CH4 ), a potent greenhouse gas, to the atmosphere. However, large uncertainties still exist regarding the response of CH4 emissions to the increasing trophic levels of lakes as well as the underlying mechanisms. Here, we investigate the CH4 emission flux from lakes with different trophic states in the middle and lower reaches of the Yangtze River basin, China to evaluate the effect of the trophic lake index ( TLI ) on CH4 emissions. The mean CH4 emission fluxes from mesotrophic, eutrophic, middle-eutrophic, and hyper-eutrophic lakes were 0.1, 4.4, 12.0, and 130.4 mg m −2 h −1, respectively. Thus, the CH4 emission flux ranged widely and was positively correlated with the degree of eutrophication. The relative abundance of methanogens with respect to the total population for the mesotrophic, eutrophic, mid-eutrophic, and hyper-eutrophic states was 0.03%, 0.35%, 0.94%, and 1.17%, respectively. The biogeographic-scale pattern of lakes classified as each of these four trophic states indicated that CH4 emissions could be well-predicted by the NH4 + -N concentration in the water column, as both NH4 + -N and CH4 were produced during mineralisation of labile organic matter in lake sediment. In addition, the shift from clear to turbid water, which is an unhealthy evolution for lakes, was associated with a nonlinear increase in the CH4 emissions from the studied lakes. In particular, the hypereutrophic lakes functioned as CH4 emission hotspots. Our findings highlight that nutrient levels, as a potential facilitator of CH4 emissions, should be considered in future research to accurately evaluate the greenhouse gas emissions from shallow lakes. Graphical abstract: Image 1 Highlights: A nonlinear model is constructed for CH4 emissions across lake trophic states. One-level increase of the trophic lake index leads to a 10-fold increase in CH4 emissions. Hypereutrophic lakes have a great potential to produce high CH4 emissions. Changes in the abundances of methanogens and methanotrophs increase CH4 emissions.